Thermodynamics and kinetics guided probe design for uniformly sensitive and specific DNA hybridization without optimization - Xin Chen (Nature Portfolio, 2019)
Optimisation of nucleic acid probes and blocker strands can be laborious. Here the authors construct a theoretical model of competitive DNA hybridisation to design DNA probes for optimisation-free mutation detection.